The Association of Dual Antiplatelet Therapy (DAPT) Duration with Ischemic and Bleeding Events Following Percutaneous Coronary Intervention (PCI): A Systematic Review - Made Ngurah Bagus Sapta Nurgita (International Medical Journal Corp. Ltd, 2025)
Introduction: Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) profoundly increases susceptibility to opportunistic ocular infections, most notably Cytomegalovirus (CMV) retinitis. The degree of immunosuppression, particularly CD4+ T-cell counts below 50 cells/μL, is the primary risk determinant. Despite advances in antiretroviral therapy (ART), CMV retinitis remains a leading cause of vision loss in advanced AIDS, especially in resource-limited settings. Methods: A systematic review was conducted by performing a PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library search across over 138 million academic papers. 40 studies meeting predefined inclusion criteria—focusing on HIV/AIDS populations, quantitative ocular outcome data, and appropriate study designs—were selected for final analysis. Data on study design, population characteristics, ocular manifestations, risk factors, diagnostics, treatments, and outcomes were extracted and synthesized. Results: CMV retinitis is the most common intraocular infection in AIDS, with a pooled prevalence of 14.0% in low- and middle-income countries. A majority (73.4%) of cases occur at CD4+ counts <50 cells/μL. Vision loss affects approximately one-third of patients. Treatment modalities include systemic antivirals (ganciclovir, valganciclovir, foscarnet, cidofovir), local therapies (intraocular implants, intravitreal injections), and combination regimens. Ganciclovir implants demonstrated the longest median time to disease progression (191-226 days). ART, particularly protease inhibitors, drastically reduces the incidence and recurrence of CMV retinitis. For patients achieving sustained immune reconstitution (CD4+ >75 cells/μL on ART for ≥18 months), discontinuation of CMV maintenance therapy is safe with a low relapse risk. Discussion: The relationship between HIV/AIDS and CMV retinitis is directly mediated by immunosuppression. Disparities in prevalence across settings are explained by late HIV diagnosis and ART initiation. Optimal management balances superior local control (e.g., implants) with systemic protection against contralateral and extraocular disease. In resource-limited settings, intravitreal injections offer a viable alternative. Crucially, early screening and diagnosis, prior to significant vision loss, are paramount as visual outcomes are largely determined by timing of intervention rather than treatment choice alone. Conclusion: CMV retinitis remains a significant cause of morbidity in advanced HIV/AIDS, tightly linked to severe immunosuppression. Successful management hinges on early diagnosis through regular ophthalmologic screening in high-risk patients (CD4+ <100 cells/μL), prompt initiation of combined local and systemic antiviral therapy, and sustained immune recovery via ART. Future efforts should focus on improving early HIV detection, expanding access to ART and antiviral therapies in resource-limited regions, and standardizing screening protocols to prevent irreversible blindness.